1996
DOI: 10.1007/bf00351173
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis sera recognize not only gp210 but also proteins of the p62 complex bearing N-acetylglucosamine residues from rat liver nuclear envelope

Abstract: We have recently observed reactivity of primary biliary cirrhosis (PBC) sera with several proteins bearing N-acetylglucosamine residues from rat liver nuclear envelopes. The aim of this study was to characterize the reactive antigens. Sera from 31 patients with PBC, 30 with rheumatoid arthritis (RA) and 30 with Sjögren's syndrome (SS) were examined. Rim-like immunofluorescence staining was observed in 15 of 31 (48%) sera from patients with PBC, in 1 of 30 with RA and in 1 of 30 with SS. Upon immunoblotting usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
6

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
0
32
0
6
Order By: Relevance
“…26 Using NPC extracts as the antigen source in immunoblotting assays, the most prominent reactivities had 60 and 200 kd apparent molecular masses, thus suggesting the presence of antibodies directed against the gp210 protein and the nucleoporin p62. 29,31,32 Further, we previously demonstrated that preabsorption of anti-NPC-positive sera with proteins extracted from freshly isolated NPC completely abolished the immunoblotting signal. 14 Similar to what was observed in our previous work, several other bands were detected when anti-NPC-positive sera were tested via immunoblotting; however, these were rare occurences, and their intensities were weaker.…”
Section: Methodsmentioning
confidence: 91%
“…26 Using NPC extracts as the antigen source in immunoblotting assays, the most prominent reactivities had 60 and 200 kd apparent molecular masses, thus suggesting the presence of antibodies directed against the gp210 protein and the nucleoporin p62. 29,31,32 Further, we previously demonstrated that preabsorption of anti-NPC-positive sera with proteins extracted from freshly isolated NPC completely abolished the immunoblotting signal. 14 Similar to what was observed in our previous work, several other bands were detected when anti-NPC-positive sera were tested via immunoblotting; however, these were rare occurences, and their intensities were weaker.…”
Section: Methodsmentioning
confidence: 91%
“…Nucleoporin p62 antibodies seem to be characteristic of patients with primary biliary cirrhosis (PBC) (4,10). In addition, four cases of Sjögren syndrome (6) and two cases of systemic lupus erythematosus (4) with p62 antibodies have been described.…”
mentioning
confidence: 99%
“…It was shown that 100% of PBC, 70% of RA, and 97% of Sjs sera reacted with some proteins in a rat liver NE fraction. 2 We have reported that some PBC, RA, and Sjs sera react with several GlcNAc-bearing proteins in rat liver NE (27). Thus, we examined the reactivities of PBC, RA, and Sjs sera with Xenopus egg extract proteins and found that these sera react with many proteins in both Xenopus egg membrane and cytosol fractions and inhibit nuclear assembly in a Xenopus egg extract cell free system to various degrees.…”
Section: Analysis Of Proteins Participating In Nuclear Assembly Bymentioning
confidence: 94%
“…Therefore, if we could obtain specific antibodies against these proteins, we would have very powerful tools for analyzing the reaction mechanism. It is known that autoimmune disease sera react with many proteins in the NE (25)(26)(27) and cytosol fractions. We applied such sera to an in vitro Xenopus egg extract nuclear assembly system and found that most sera suppressed the assembly to various extents.…”
Section: The Nuclear Envelope (Ne)mentioning
confidence: 99%